Peran identitas halal dalam membentuk perilaku pembelian konsumen pada produk perawatan diri - Cahyaning Budi Utami; Slamet Slamet; Rebecca Cindy Sartika; Muh Syaiful Bakhri (Nur Science Institute, 2025)
The halal personal care industry in Indonesia has recorded rapid growth in recent years, as evidenced by the increasing number of locally halal-certified brands and a noticeable shift in consumer preferences toward prioritising product safety and halal identity. This market dynamic highlights the need to better understand the factors that shape consumer purchasing behaviour. This study aims to examine the influence of internal product characteristics, namely price and halal labelling, and external factors, including perceived product quality and halal awareness, on purchase behaviour, with purchase intention serving as a mediating variable. This study targeted individuals within the productive age group who consume halal personal care products. Data were collected via an online questionnaire administered to 144 respondents and analysed using the Partial Least Squares–Structural Equation Modelling (PLS-SEM) approach. The results indicate that halal awareness and halal labels significantly influence purchase intention, whereas perceived product quality and price do not. Furthermore, purchase intention is shown to be a crucial mediator linking halal awareness and halal label to actual purchase behaviour. These findings underscore that consumer purchase behaviour in this category is driven more by value orientation and halal identity than by functional product considerations.